CONDITIONAL SENTENCE WITH PROTECTIVE SUPERVISION - concept, application, and relationship with other alternative sanctions and measures - Olga Tešović (Revija za kriminologiju i krivično pravo)
The paper gives an overview of the concept and content of a conditional sentence with protective supervision according to the solutions in the Criminal Code of the Republic of Serbia, pointing out certain substantive inconsistencies and legal gaps. The author explains what significance this sanction should have in the system of non-custodial sanctions and measures, starting from international standards and comparative practice in this area. In addition to substantive law, the paper also analyzes the regulations related to the execution of this alternative sanction, as well as the situation with its application in practice. Special attention was given to the relationship of this alternative sanction with other alternative sanctions and measures, both with those that already exist in our positive law - house arrest, work in the public interest and the institute of settlement of perpetrators and injured parties, and with some non-custodial measures which originate from the Anglo-Saxon legal field - „shaming punishments“, which exist in the USA law. The aim of this paper is to point out the importance of this alternative sanction and its possibilities of improvement in terms of greater and more efficient application in practice.